Lithium ion conductive glass material

By using lithium -ion -electrical glass materials containing specific ingredients in lithium ion secondary batteries and lithium ion -conductive materials for low -temperature mixing sintering, solving the safety problem of liquid electrolytes and the problem of electrode active material decomposition caused by high temperature sintering. The solid electrolyte of high density and high -lithium ion conductivity improves the safety and mass production of the battery.

CN119365429APending Publication Date: 2025-01-24OHARA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380046925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-21
Filing Date
2023-06-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The liquid electrolyte used in existing lithium-ion secondary batteries has safety problems such as electrolyte leakage and organic solvent volatility, and high-temperature sintering leads to decomposition of electrode active substances.

Method used

A lithium ion conductive glass material containing 43.5% to 49.0% P2O5, 0.5% to 4.0% Al2O3 and 47.0% to 55.0% Li2O is mixed and sintered below 700°C to form a high density and Solid electrolyte with high lithium ion conductivity.

Benefits of technology

It achieves the formation of a solid electrolyte with high density and high lithium ion conductivity under low-temperature sintering conditions, avoids the decomposition of electrode active materials, and improves the safety and mass production of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365429A_ABST
    Figure CN119365429A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion conductivity glass material which can form a solid electrolyte with high lithium ion conductivity by mixing and sintering with a lithium ion conductivity material at 700 DEG C or below. According to the present invention, the technical problem is solved by using the lithium ion conductivity glass material, which comprises, by mol% on the basis of the oxide, 43.5-49.0% of a P2O5 component, 0.5-4.0% of an Al2O3 component, and 47.0-55.0% of a Li2O component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium ion conductive glass material, a solid electrolyte material comprising the material, or an electrode active material having a coated glass layer formed by coating the material, and also relates to an all-solid-state secondary battery, which includes a component formed by sintering a material containing the solid electrolyte material. Background Art

[0002] Lithium-ion secondary batteries, which have high energy density and are rechargeable and dischargeable, are widely used in applications such as power sources for electric vehicles and mobile phone terminals.

[0003] Most of the lithium-ion secondary batteries currently on the market use a liquid electrolyte (electrolyte) in order to have a high energy density. In addition, as the electrolyte, an electrolyte obtained by dissolving a lithium salt in an aprotic organic solvent such as carbonate or cyclic ester is generally used.

[0004] However, in lithium ion secondary batteries (liquid lithium ion secondary batteries) using liquid electrolytes (electrolyte), there is a risk of electrolyte leakage. In addition, organic solvents and the like generally used in electrolytes are volatile and combustible substances, which are undesirable in terms of safety.

[0005] Therefore, as the electrolyte of lithium-ion secondary batteries, it is proposed to use solid electrolytes to replace liquid electrolytes (electrolytes) such as organic solvents. In addition, the development of all-solid-state secondary batteries that use solid electrolytes as electrolytes and other components such as electrode layers are also all solid-state is also ongoing.

[0006] It should be noted that, as representative characteristics required of the solid electrolyte of the all-solid-state secondary battery, lithium ion conductivity and sintering characteristics can be cited. In addition, in order to form a good interface with the electrode layer (positive electrode layer and negative electrode layer), the material other than the solid electrolyte material of the electrode active material and the solid electrolyte material form a good interface, and the solid electrolyte materials in the electrode layer or in the solid electrolyte layer form a good interface with each other, etc., its density needs to be above a certain value.

[0007] Furthermore, as a solid electrolyte for an all-solid-state secondary battery, for example, Li 1+ x Al x Ti 2-x P3O 12 Glass ceramic electrolytes with AlPO4 added thereto have been studied. In addition, as shown in Non-Patent Documents 2, 3 and Patent Document 1, attempts have been made to improve sintering properties by mixing lithium ion conductive glass into ceramic electrolytes in order to enable low temperature sintering.

[0008] As for lithium ion conductive glass material single substance, as shown in non-patent document 4, research has been conducted on Li2O-SiO2, Li4SiO4-Li3BO3, Li2O-SiO2-B2O3, Li2O-SiO2-ZrO2, etc. It is known that the Li2O content is beneficial to lithium ion conductivity. In recent years, as a solid electrolyte for all-solid-state secondary batteries, as shown in non-patent document 5, research has been conducted on improving water resistance by fixing the Li2O content of Li2O-Al2O3-P2O5 glass at 50 mol% and increasing the Al2O3 content. Similarly, as shown in patent document 2, research has been conducted on improving water resistance by adding ZrO2 components, Y2O3 components, CeO2 components, etc. to Li2O-Al2O3-P2O5 glass.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2012-209256

[0012] Patent Document 2: Japanese Patent Application Publication No. 2015-153588

[0013] Non-patent literature

[0014] Non-patent document 1: Journal of the American Ceramic Society (J.Am.Ceram.Soc.) 80 (1997) 1901-1903

[0015] Non-patent document 2: Journal of Solid State Chemistry 265 (2018) 381-386

[0016] Non-patent document 3: Solid State Ionics 47 (1991) 257-264

[0017] Non-patent literature 4: Functional Chemistry Series of Electrons and Ions Vol.3 Next Generation Lithium Ion Secondary Batteries ISBN 4-86043-023-9C3043 P276-280

[0018] Non-patent document 5: Journal of Non-crystalline Solids 430 (2015) 64-72 Summary of the invention

[0019] Technical problem to be solved by the invention

[0020] Among them, the glass ceramic electrolyte shown in Non-Patent Document 1 is reported to have a lithium ion conductivity of 1×10 -3 S / cm. However, the sintering temperature during synthesis is very high, above 1000°C. In addition, when the electrode material is re-sintered after synthesis, the lithium ion conductivity at 25°C is maintained at 1×10 -4 S / cm or so requires a sintering temperature of 900°C or above, and there is a problem of high-temperature sintering causing decomposition of the electrode active material (positive electrode active material or negative electrode active material).

[0021] On the other hand, the ceramic electrolytes shown in non-patent documents 2 and 3 have very low intragranular resistance (resistance of ion conduction occurring within the grains), but high grain boundary resistance (resistance of ion conduction occurring at the contact interface between grains), making it difficult to maintain high lithium ion conductivity. Therefore, the grain boundary resistance is reduced and lithium ion conductivity is increased by mixing and sintering lithium salts such as Li3PO4 and Li3BO3 and lithium ion conductive glasses such as Li3BO3 glass. However, in this way, 1×10 -4 The sintering temperature required for a lithium ion conductivity of about S / cm is also quite high, at 900°C.

[0022] In addition, Patent Document 1 discloses an all-solid-state secondary battery that mixes two solid electrolytes, among which a solid electrolyte using a lithium ion conductive glass material of the Li2O-P2O5 system is disclosed. Moreover, although its sintering temperature is relatively low at 600°C, it needs to be pressurized at high temperatures, so it lacks mass production.

[0023] Furthermore, Patent Document 2 discloses that water resistance is improved and the discharge capacity of the all-solid-state secondary battery is improved by making Li2O-P2O5-Al2O3 glass contain one or more selected from Y2O3, Sc2O3, ZrO, CeO2 and Sm2O3. However, although the sintering temperature is relatively low at 600°C, it also lacks mass production due to the need for pressurization at high temperatures.

[0024] It is known that as a method for improving mass productivity, it is preferable to form sheets, stack, cut, degrease, and then sinter them in the same manner as a laminated ceramic capacitor. However, sintering at 700° C. or lower is required to suppress diffusion of materials (Journal of Power Sources 192 (2009) 689-692).

[0025] Therefore, an object of the present invention is to provide a lithium ion conductive glass material, which can form a solid electrolyte having both high density and high lithium ion conductivity by mixing and sintering the glass material with a lithium ion conductive material at a temperature below 700°C.

[0026] Solutions to technical problems

[0027] In order to solve the above technical problems, the inventors have found through in-depth research that a lithium ion conductive glass material containing 43.5% to 49.0% of P2O5, 0.5% to 4.0% of Al2O3 and 47.0% to 55.0% of Li2O, calculated as mol% on an oxide basis, can be used as a sintering aid and mixed with a lithium ion conductive material for sintering at a temperature below 700° C. to form a solid electrolyte having both high density and high lithium ion conductivity. Furthermore, it has been found that the lithium ion conductive glass material can also be used as a material for coating the surface of an electrode active material.

[0028] That is, the present invention is as follows <1> to <7>.

[0029] <1> A lithium ion conductive glass material, which contains, based on mol% of oxides, 43.5% to 49.0% of P2O5, 0.5% to 4.0% of Al2O3, and 47.0% to 55.0% of Li2O.

[0030] <2>. The lithium ion conductive glass material as described in <1>, wherein the material satisfies at least two selected from the group consisting of (1), (2) and (3) below, and the lithium ion conductivity at 25° C. in the glass state is 5.0×10 -9 S / cm or more 5.0×10 -8 S / cm or less,

[0031] (1) The crystallization temperature (Tc) is 400°C to 460°C;

[0032] (2) Glass transition point (Tg) is above 330°C and below 365°C;

[0033] (3) The melting start temperature (mp) is 560°C or higher and 590°C or lower.

[0034] <3>. The lithium ion conductive glass material as described in <1> or <2>, wherein the lithium ion conductive glass material is a crystalline phase of a NASICON structure including a rhombohedral crystal system, Li 1+x Al x Ti 2-x P3O 12 (0.7>x≥0.05) crystalline phase, or Li 1+x+y Al x Ti 2-x Si y P 3-y O 12The sintering aid is used for mixed sintering of a lithium ion conductive material having a crystalline phase of (0.7>x≥0.05, 0.5>y≥0), wherein the lithium ion conductive glass material has a maximum particle diameter of 200 μm or less and an average particle diameter (D 50 ) Powders below 100 μm.

[0035] <4> A solid electrolyte material obtained by mixing the lithium ion conductive glass material as described in any one of <1> to <3> with a lithium ion conductive material, wherein the lithium ion conductive material comprises: a crystal phase of a rhombohedral NASICON structure, Li 1+x Al x Ti 2-x P3O 12 (0.7>x≥0.05) crystalline phase, or Li 1+x+y Al x Ti 2- x Si y P 3-y O 12 (0.7>x≥0.05, 0.5>y≥0) crystalline phase.

[0036] <5> An all-solid-state secondary battery comprising a component integrally formed by sintering a material including the solid electrolyte material according to <4> and a positive electrode material or a negative electrode material.

[0037] <6>. An electrode active material (positive electrode active material or negative electrode active material), comprising a coating glass layer formed by coating the lithium ion conductive glass material as described in <1> or <2> on the surface, wherein the coating rate of the coating glass layer on the surface is 18% or more.

[0038] <7>. A lithium ion secondary battery (an all-solid-state secondary battery or a liquid lithium ion secondary battery using a liquid electrolyte), comprising the electrode active material described in <6>.

[0039] Effects of the Invention

[0040] According to the present invention, a lithium ion conductive glass material can be provided, which can form a solid electrolyte having both high density and high lithium ion conductivity by mixing and sintering the lithium ion conductive glass material with a lithium ion conductive material at a temperature below 700° C. In addition, the lithium ion conductive glass material is suitable for use as a coating glass layer for coating the surface of an electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a synthesis flow chart of the lithium ion conductive glass material (step 1) and the solid electrolyte (step 2) of the embodiment and the comparative example.

[0042] Figure 2 This is a graph showing the relationship between the P2O5 content (mol%) and the Li2O content (mol%) of the lithium ion conductive glass materials of the examples and comparative examples.

[0043] Figure 3 This is a graph showing the relationship between the Al2O3 content (mol%) and the Li2O content (mol%) of the lithium ion conductive glass materials of Examples and Comparative Examples.

[0044] Figure 4 This is a graph showing the relationship between the Li2O content (mol%) and the lithium ion conductivity (ion conductivity of glass) of the lithium ion conductive glass materials of Examples and Comparative Examples.

[0045] Figure 5 This is a graph showing the relationship between the crystallization temperature (Tc) and the melting start temperature (mp) of the lithium ion conductive glass materials of Examples and Comparative Examples.

[0046] Figure 6 This is a graph showing the relationship between the crystallization temperature (Tc) and the glass transition point (Tg) of the lithium ion conductive glass materials of Examples and Comparative Examples.

[0047] Figure 7 This is a graph showing the relationship between the lithium ion conductivity (ion conductivity) and the density of the sintered particles of Examples and Comparative Examples.

[0048] Figure 8 This is a graph showing the relationship between the P2O5 content (mol%) of the lithium ion conductive glass material used in the production of sintered particles in Examples and Comparative Examples and the density of the sintered particles.

[0049] Fig. 9 This is a graph showing the relationship between the Li2O content (mol %) of the lithium ion conductive glass material used in the production of sintered particles in Examples and Comparative Examples and the density of the sintered particles.

[0050] Fig.10 This is a graph showing the relationship between the lithium ion conductivity (ion conductivity of glass) of the lithium ion conductive glass material used for producing the sintered body particles of Examples and Comparative Examples and the density of the sintered body particles.

[0051] Fig.11 These are secondary electron images (photographs used as drawings) of cross sections of sintered particles of Examples and Comparative Examples obtained by sintering at 700°C.

[0052] Fig.12This is a graph showing the relationship between the Al2O3 content (mol%) of the lithium ion conductive glass material used in the production of sintered particles in Examples and Comparative Examples and the density of the sintered particles.

[0053] Fig.13 This is a graph showing the relationship between the lithium ion conductivity (ion conductivity of glass) of the lithium ion conductive glass material used for producing the sintered body particles of Examples and Comparative Examples and the lithium ion conductivity (ion conductivity) of the sintered body particles.

[0054] Fig.14 This is a graph showing the relationship between the glass transition point (Tg) of the lithium ion conductive glass material used for preparing the sintered particles of Examples and Comparative Examples, and the lithium ion conductivity (ion conductivity) and density of the sintered particles.

[0055] Fig.15 This is a graph showing the relationship between the crystallization temperature (Tc) of the lithium ion conductive glass material used for preparing the sintered particles of Examples and Comparative Examples, and the lithium ion conductivity (ion conductivity) and density of the sintered particles.

[0056] Fig.16 This is a graph showing the relationship between the melting start temperature (mp) of the lithium ion conductive glass material used for producing the sintered particles of Examples and Comparative Examples, and the lithium ion conductivity (ion conductivity) and density of the sintered particles. DETAILED DESCRIPTION

[0057] The present invention will be described.

[0058] The present invention is a lithium ion conductive glass material, which contains, in terms of mol% based on oxides, 43.5% to 49.0% of a P2O5 component, 0.5% to 4.0% of an Al2O3 component, and 47.0% to 55.0% of a Li2O component. In other words, the lithium ion conductive glass material contains, in terms of mol% based on oxides, 43.5% to 49.0% of a P2O5 component, 0.50% to 4.0% of an Al2O3 component, and 47.0% to 55.0% of a Li2O component in a manner that satisfies all of the above conditions simultaneously.

[0059] Hereinafter, they are sometimes referred to as "lithium ion conductive glass materials of the present invention".

[0060] It should be noted that the content of each component contained in the lithium ion conductive glass material of the present invention is expressed in terms of mol% based on the oxide unless otherwise specified. It should be noted that the content expressed in terms of "mol% based on the oxide" means that, assuming that all oxides, complex salts, metal fluorides, etc. used as raw materials for the lithium ion conductive glass material of the present invention are decomposed into oxides during melting, the total number of moles (total mass) of the generated oxides is taken as 100 mol%, and the content of each component contained in the lithium ion conductive glass material of the present invention is expressed.

[0061] <Ingredients>

[0062] First, each component constituting the lithium ion conductive glass material of the present invention will be described.

[0063] The P2O5 component is an essential component necessary for the lithium ion conductive glass material of the present invention to form glass, and is a component capable of adjusting the glass transition point (Tg). In addition, it is also a component that promotes crystallization during low-temperature co-sintering with the lithium ion conductive material and easily increases the density of the obtained solid electrolyte. Therefore, the content of the P2O5 component has a lower limit of 43.5 mol%, preferably 43.8 mol%, more preferably 44.0 mol%, even more preferably 44.2 mol%, even more preferably 45.0 mol%, further preferably 45.5 mol%, and even more preferably 46.0 mol%. On the other hand, from the viewpoint of avoiding the reduction of the lithium ion conductivity or density of the solid electrolyte obtained by low-temperature co-sintering with the lithium ion conductive material due to excessive content, the upper limit of the content of the P2O5 component is 49.0 mol%, preferably 48.5 mol%, more preferably 48.3 mol%, even more preferably 48.0 mol%, even more preferably 47.5 mol%, further preferably 47.0 mol%, and even more preferably 46.5 mol%.

[0064] The Al2O3 component is also an essential component necessary for the lithium ion conductive glass material of the present invention to form glass, and is a component capable of adjusting the melting start temperature (mp). In addition, it is also a component capable of adjusting the lithium ion conductivity of the lithium ion conductive glass material of the present invention. Therefore, the lower limit of the content of the Al2O3 component is 0.5 mol%, preferably 0.8 mol%, more preferably 1.0 mol%, still more preferably 1.5 mol%, and further preferably 1.7 mol%. On the other hand, from the viewpoint of avoiding the reduction of the lithium ion conductivity of the solid electrolyte obtained by low-temperature mixing and sintering with the lithium ion conductive material due to excessive content, the upper limit of the content of the Al2O3 component is 4.0 mol%, preferably 3.5 mol%, more preferably 3.3 mol%, still more preferably 3.0 mol%, and further preferably 2.7 mol%.

[0065] The Li2O component is an essential component necessary to impart lithium ion conductivity to the lithium ion conductive glass material of the present invention. Therefore, the lower limit of the content of the Li2O component is 47.0 mol%, preferably 47.5 mol%, more preferably 48.0 mol%, and even more preferably 48.5 mol%. On the other hand, from the viewpoint of improving the chemical durability of the lithium ion conductive glass material of the present invention, the upper limit of the content of the Li2O component is 55.0 mol%, preferably 54.5 mol%, more preferably 54.0 mol%, even more preferably 53.8 mol%, even more preferably 53.5 mol%, further preferably 53.0 mol%, further more preferably 52.5 mol%, and even more preferably 52.0 mol%.

[0066] It should be noted that, from the viewpoint of making it easier to exert the effects of the present invention, the lithium ion conductive glass material of the present invention preferably has a higher content of the Li2O component than the content of the P2O5 component in its composition. At the same time, the ratio of the total content of the Al2O3 component and the Li2O component to the content of the P2O5 component ((Al2O3 component + Li2O component) / P2O5 component, molar ratio) is preferably 1.05 or more, more preferably 1.08 or more, and even more preferably 1.15 or more. In addition, the upper limit is preferably 1.30 or less, more preferably 1.28 or less, and even more preferably 1.26 or less.

[0067] The lithium ion conductive glass material of the present invention may be composed of the essential components described above, and may also contain, as an optional component, one or more selected from the group consisting of a SiO2 component, a B2O3 component, a Nb2O5 component, a GeO2 component, a La2O3 component, a Sc2O3 component, a Y2O3 component, a CeO2 component, a MgO component, a CaO component, a SrO component, a ZrO2 component, a TiO2 component, a SnO2 component, a V2O5 component, a Fe2O3 component, a Fe2O4 component, a Mn3O4 component, a Mn2O7 component, a CoO component, a Co2O3 component, and a Bi2O3 component.

[0068] The SiO2 component, the B2O3 component, the GeO2 component, the Nb2O5 component and the La2O3 component are all arbitrary components that make it easy for the lithium ion conductive glass material of the present invention to form glass. Therefore, it is possible to replace (displace) a part of the P2O5 component. In addition, the Nb2O5 component is also a component that can adjust the glass transition point (Tg) and the melting start temperature (mp). In addition, the SiO2 component can also improve the mechanical strength of the solid electrolyte obtained by low-temperature mixed sintering with the lithium ion conductive material. It should be noted that the content of the SiO2 component is preferably 5.0 mol% or less, more preferably 3.0 mol% or less, and even more preferably 2.0 mol% or less. In addition, the contents of the B2O3 component, the GeO2 component, the Nb2O5 component and the La2O3 component are each preferably 9.0 mol% or less, more preferably 8.0 mol% or less, even more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and even more preferably 2.0 mol% or less.

[0069] The Sc2O3 component, the Y2O3 component, and the CeO2 component can replace (displace) a part of the Al2O3 component, and are arbitrary components that can adjust the lithium ion conductivity of the lithium ion conductive glass material of the present invention. It should be noted that the contents of the Sc2O3 component, the Y2O3 component, and the CeO2 component are preferably 9.0 mol% or less, more preferably 8.0 mol% or less, even more preferably 5.0 mol% or less, further preferably 3.0 mol% or less, and even more preferably 2.0 mol% or less.

[0070] MgO, CaO and SrO can also replace (displace) a part of Al2O3 and are arbitrary components that can further improve the lithium ion conductivity of the lithium ion conductive glass material of the present invention. In addition, they are also components that can adjust the glass transition point (Tg) and the melting start temperature (mp). It should be noted that the content of MgO, CaO and SrO is preferably 9.0 mol% or less, more preferably 8.0 mol% or less, still more preferably 5.0 mol% or less, further preferably 3.0 mol% or less, and further preferably 2.0 mol% or less.

[0071] The ZrO2 component, the TiO2 component, and the SnO2 component are all arbitrary components that can impart water resistance to the lithium ion conductive glass material of the present invention. In addition, the ZrO2 component is also beneficial to improving the chemical durability of the lithium ion conductive glass material of the present invention. It should be noted that the content of the ZrO2 component is preferably 0.5 mol% or more, more preferably 1.0 mol% or more, and even more preferably 2.0 mol% or more, based on the viewpoint that the chemical durability of the lithium ion conductive glass material of the present invention can also be improved when it is in powder form. On the other hand, based on the viewpoint that the melting temperature when the raw material is melted can be set lower and devitrification during casting (glass block formation) can be easily suppressed, it is preferably 9.0 mol% or less, more preferably 8.0 mol% or less, even more preferably 5.0 mol% or less, and further preferably 3.0 mol% or less. In addition, the contents of TiO2 and SnO2 are each preferably 9.0 mol% or less, more preferably 8.0 mol% or less, still more preferably 5.0 mol% or less, further preferably 3.0 mol% or less, and further preferably 2.0 mol% or less.

[0072] The V2O5 component, the Fe2O3 component, the Fe2O4 component, the Mn3O4 component, the Mn2O7 component, the CoO component, the Co2O3 component, and the Bi2O3 component are all arbitrary components that can impart functionality (such as inhibiting the reaction with the electrode active material) to the lithium ion conductive glass material of the present invention. It should be noted that the contents of these components are preferably 9.0 mol% or less, more preferably 8.0 mol% or less, still more preferably 5.0 mol% or less, further preferably 3.0 mol% or less, and further preferably 2.0 mol% or less.

[0073] It should be noted that the lithium ion conductive glass material of the present invention preferably has a sulfur (S) content as low as possible (for example, less than 1.0 mol%, further less than 0.1 mol%, etc.), and more preferably does not contain it. This is because by reducing the S component, the possibility of the generation of harmful gases such as hydrogen sulfide can be reduced in the all-solid-state secondary battery, etc. using the lithium ion conductive glass material of the present invention as a raw material. In addition, in order to avoid the reduction of lithium ion conductivity, etc., it is also preferred to reduce alkali metals (Na, K, etc.) other than Li as much as possible, and more preferably not contain it. In addition, it is also preferred to reduce zinc (Zn), arsenic (As), antimony (Sb) and lead (Pb) as much as possible, and more preferably not contain them. This is because they can become harmful substances, and zinc (Zn) can also become a component that reduces lithium ion conductivity.

[0074] Furthermore, the lithium ion conductive glass material of the present invention having the above-mentioned components and composition is a material in a glass state (amorphous state). In other words, it is an oxide-based glass material (glass electrolyte) having lithium ion conductivity. Therefore, the lithium ion conductive glass material of the present invention does not substantially contain a crystalline phase.

[0075] <Physical properties and form>

[0076] Next, the physical properties and morphology of the lithium ion conductive glass material of the present invention are described in detail.

[0077] The lithium ion conductive glass material of the present invention preferably has a crystallization temperature (Tc) of 400°C to 460°C, a glass transition point (Tg) of 330°C to 365°C, and a melting start temperature (mp) of 560°C to 590°C. In addition, from the viewpoint of making it easier to improve the lithium ion conductivity and density of a solid electrolyte obtained by low-temperature mixing and sintering with a lithium ion conductive material at 700°C or less, it is preferred that at least two or more selected from the group consisting of the above three thermophysical properties (predetermined crystallization temperature, predetermined glass transition point, and predetermined melting start temperature) are satisfied, and it is particularly preferred that all three thermophysical properties are satisfied.

[0078] Furthermore, the crystallization temperature (Tc) is more preferably 410°C or more, even more preferably 420°C or more, and further preferably 430°C or more. In addition, it is more preferably 455°C or less, even more preferably 450°C or less, and further preferably 440°C or less. The glass transition point (Tg) is more preferably 335°C or more, even more preferably 338°C or more, and further preferably 340°C or more. In addition, it is more preferably 360°C or less, even more preferably 355°C or less, and further preferably 350°C or less. The melting start temperature (mp) is more preferably 562°C or more. In addition, it is more preferably 587°C or less, even more preferably 575°C or less, and further preferably 570°C or less.

[0079] Here, these crystallization temperatures (Tc), glass transition points (Tg) and melting start temperatures (mp) are all values ​​measured by differential scanning calorimetry using TG-DTA2000SA manufactured by Bruker Corporation. In addition, these crystallization temperatures (Tc), glass transition points (Tg) and melting start temperatures (mp) can be adjusted by the composition of the components described above.

[0080] Furthermore, since the lithium ion conductive glass material of the present invention is used for manufacturing a solid electrolyte by mixing and sintering with a lithium ion conductive material containing a predetermined crystal phase and plays a role in lithium ion conduction when an interface is formed, the lithium ion conductivity of the glass material in the glass state at 25° C. (lithium ion conductivity of the glass material before low-temperature mixing and sintering) is preferably 5.0×10 -9 S / cm or more, more preferably 8.0×10 -9 S / cm or more, and more preferably 1.0×10 -8 In addition, when mixed with a lithium ion conductive material containing a predetermined crystal phase and sintered, the upper limit is preferably 5.0×10 -8 S / cm or less, more preferably 4.0×10 -8 S / cm or less, and more preferably 3.5×10 -8 It should be noted that even when at least two or more selected from the group of the above three thermophysical properties are not satisfied (one or less is satisfied), the lithium ion conductivity at 25° C. in the glass state is preferably within the above range.

[0081] Furthermore, the lithium ion conductive glass material of the present invention can be used as a sintering aid (sintering aid for low temperature sintering) etc. which is mixed with a lithium ion conductive material and sintered at a low temperature below 700°C to form a solid electrolyte (oxide-based solid electrolyte). Therefore, based on the ease of low temperature mixed sintering and the ease of interface formation during the one-time sintering of an all-solid-state secondary battery, its form is preferably in powder form. The interface formation mentioned here refers to both the three-phase interface that forms the three-dimensional structure of the electrode active material, the conductive aid and the solid electrolyte, and the interface between the solid electrolyte materials. In particular, when constituting an all-solid-state secondary battery, based on the viewpoints of forming the interface at a lower temperature, further increasing the reaction interface, and further reducing the thickness of the electrolyte layer film, the average particle diameter (D 90 ) is preferably 2 μm or less (e.g., 1 μm or more and 2 μm or less), and the average particle diameter (D 50 ) is preferably about 1 μm (for example, 2 μm or less, further 1.5 μm or less, and further 1 μm or less).

[0082] It should be noted that, although sheet molding is sometimes used when constructing an all-solid-state secondary battery, it is also preferred to use the powdered lithium ion conductive glass material of the present invention as a sheet molding material. In this case, in view of weather resistance, in order to avoid re-agglomeration of particles, etc., the maximum particle diameter of the powder is 200 μm or less, more preferably 150 μm or less, and further preferably 120 μm or less, and the average particle diameter (D 50 ) is less than 100μm, more preferably less than about 80μm, specifically preferably a product that passes through a 106μm sieve, and a powder that is crushed so that the final maximum particle diameter becomes less than 1 / 20 of the target sheet film thickness. For example, if the target sheet film thickness is 20μm, a powder with a maximum particle diameter of less than 1μm is preferred. Thus, it is easy to suppress the reaction with the atmosphere until the sheet is formed. In order to form a powder that passes through a 106μm sieve from a glass block, there is no particular limitation, and a punch mill, a ball mill, a jaw crusher, etc. can be used. The average particle diameter (D 50 ) is not limited, but considering water resistance (dissolution in water) etc., it can be 20 μm or more, and can also be 40 μm or more.

[0083] Here, the "maximum particle diameter" and "average particle diameter" of particles in the present invention refer to the maximum particle diameter and the volume-based average particle diameter (the diameter of 90% of the volume cumulative distribution (D 90 ), the diameter of the 50% cumulative volume distribution (D 50 ))).

[0084] However, the lithium ion conductive glass material of the present invention may also be a glass block (including not only amorphous block glass but also roughly fixed block glass such as plate-shaped glass). For example, a block (roughly plate-shaped) with a length and width of 10 cm×10 cm and a thickness of about 1 cm can be selected. Since the specific surface area is relatively low, it has the characteristics of low reactivity and suitable for storage. In addition, it can be transported in this state and crushed for use.

[0085] The lithium ion conductive glass material of the present invention having the above structure can be a material whose essential components are strictly adjusted as described above, and two or more selected from the crystallization temperature (Tc), glass transition point (Tg) and melting start temperature (mp) and the lithium ion conductivity in the glass state are also strictly adjusted, so by mixing and sintering with the lithium ion conductive material at a low temperature below 700°C, even without pressurization (no need to pressurize during sintering), a solid electrolyte with high density and high lithium ion conductivity can be formed. In other words, it becomes a sintering aid (sintering aid for glass electrolyte) that can form a solid electrolyte with high density and high lithium ion conductivity even by low temperature sintering below 700°C. For example, by low temperature sintering below 700°C, even without pressurization during sintering, a solid electrolyte with a density of 2.45 g / cm 3 Above, further 2.50g / cm 3 Above, further to 2.55g / cm 3 The lithium ion conductivity at 25°C is 5.0×10 -5 S / cm or more, and further 8.0×10 -5 S / cm or more, and further 1.0×10 -4 S / cm or more solid electrolytes, etc. Therefore, it is also easy to mass-produce solid electrolytes with high density and high lithium ion conductivity. In addition, since low-temperature sintering below 700°C can be performed, it can also be integrally formed with materials including electrode active materials. And, as described below, it is also suitable for use as a coating agent (coating glass layer) for electrode active materials.

[0086] It should be noted that the lithium ion conductive material used for mixed sintering with the lithium ion conductive glass material of the present invention is not particularly limited. When the solid electrolyte is prepared by low-temperature mixed sintering at 700° C. or below, it is preferred to use a LATP-based lithium ion conductive material, for example, a crystalline phase of a NASICON structure of a rhombohedral crystal system, a Li 1+x Al x Ti 2-x P3O 12(0.7>x≥0.05) crystalline phase, or Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 In other words, the lithium ion conductive glass material of the present invention is combined with a crystal phase of a NASICON structure of a rhombohedral system, a Li 1+x Al x Ti 2-x P3O 12 (0.7>x≥0.05) crystalline phase, or Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 A solid electrolyte material obtained by mixing a lithium ion conductive material having a crystalline phase with (0.7>x≥0.05, 0.5>y≥0) is preferred. In this case, the lithium ion conductive glass material of the present invention used for mixing preferably has a maximum particle diameter of 200 μm or less and an average particle diameter (D 50 ) is a powder of 100 μm or less. Here, the "glass ceramics" mentioned above include a crystalline phase and an amorphous phase (non-crystalline phase) formed by heat treatment. The crystalline phase is a crystalline phase obtained by heat treating a glass material (amorphous material) as a raw material so that a crystalline phase is precipitated, or a crystalline phase synthesized by heat treating a glass material and other materials. In other words, it is a mixture of ceramics and glass.

[0087] Furthermore, the crystal phase of the NASICON structure including the rhombohedral crystal system, Li 1+x Al x Ti 2-x P3O 12 (0.7>x≥0.05) crystalline phase or Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 In the lithium ion conductive material of the crystalline phase of (0.7>x≥0.05, 0.5>y≥0), x in the above formula is more preferably 0.6 or less, and further preferably 0.5 or less. In addition, the lower limit of x is more preferably 0.1 or more. Furthermore, y in the above formula is more preferably 0.4 or less, and further preferably 0.3 or less.

[0088] In addition, the lithium ion conductive material may also contain a portion of lithium ion conductive crystalline phases of other structures (for example, LISICON type, perovskite type, garnet type, etc.). However, even in this case, among all the crystalline phases (all crystalline phases) contained in the lithium ion conductive material, the above-mentioned crystalline phase is more preferably 80 mass % or more, still more preferably 90 mass % or more, further preferably 95 mass % or more, and further preferably 99 mass % or more. In other words, it is preferred that the above-mentioned crystalline phase is the main crystalline phase. In addition, the crystalline phase contained in the lithium ion conductive material may also be substantially composed of the crystalline phases described above.

[0089] Furthermore, in the low-temperature sintering at a sintering temperature below 700°C, the layers (positive electrode layer and / or negative electrode layer) and the interconnection layer that become the electrode layers of the all-solid-state secondary battery can also be integrally molded to form a component. Then, the component can be used to form an all-solid-state secondary battery. In other words, an all-solid-state secondary battery can be formed that has a component that is sintered and integrally molded with a material that includes the solid electrolyte material described above, and the positive electrode material or the negative electrode material. The electrode layer or electrode material can use a known one, for example, it can use: an electrode layer or electrode material for an all-solid-state secondary battery obtained by mixing the electrode active material (positive electrode active material or negative electrode active material) with a conductive aid, an inorganic binder, etc. as needed and then sintering it. In addition, the lithium ion conductive glass material and the lithium ion conductive material of the present invention can also obtain an electrode layer (electrode layer containing a solid electrolyte) of an all-solid-state secondary battery by low-temperature mixing and sintering with the positive electrode active material or the negative electrode active material. Furthermore, by using the lithium ion conductive glass material of the present invention as a part of the solid electrolyte material and performing low temperature sintering at 700° C. or lower, decomposition of the electrode active material and reduction in discharge capacity in the obtained all-solid secondary battery can be avoided.

[0090] It should be noted that as the positive electrode active material, there can be exemplified: NASICON type LiV2(PO4)3, olivine type Li x J y M tPO4 (wherein J is at least one selected from Al, Mg, and W, Mt is at least one selected from Ni, Co, Fe, and Mn, x satisfies 0.9≤x≤1.5, and y satisfies 0≤y≤0.2), layered oxides, spinel oxides (lithium manganese oxides, etc.), etc. In addition, as negative electrode active materials, examples include: crystalline oxides including NASICON type, olivine type, and spinel type, rutile type oxides, anatase type oxides, amorphous metal oxides, metal alloys, etc. Further, as conductive aids, examples include: carbon compounds such as graphite, activated carbon, and carbon nanotubes, at least one metal selected from Ni, Fe, Mn, Co, Mo, Cr, Ag, and Cu, their alloys, metals such as titanium or stainless steel, and aluminum, and precious metals such as platinum, gold, ruthenium, and rhodium.

[0091] Furthermore, as described above, the lithium ion conductive glass material of the present invention is also suitable for use as a coating agent for electrode active materials. That is, it can be said that it is a lithium ion conductive glass material suitable for coating treatment of electrode active materials. Furthermore, it is preferred to form the following electrode active material: it has a coating glass layer formed by coating the lithium ion conductive glass material of the present invention on the surface, and the coating rate of the coating glass layer on the surface is 18% or more. For example, in a liquid-type lithium ion secondary battery using a liquid electrolyte, there is a technical problem that the electrode active material is damaged and degraded during desolvation during charging and discharging, resulting in the cyclic degradation of the liquid-type lithium ion secondary battery. If an electrode active material having such a coating glass layer is used, the damage of the electrode active material can be suppressed. In addition, in an all-solid-state secondary battery, the electrode active material having such a coating glass layer can be mixed and sintered with a solid electrolyte material (a material containing a lithium ion conductive material) at a temperature below 700°C, so that the interface between the electrode active material and the solid electrolyte can be formed well, and its interface resistance can be further reduced, so it is preferred. In addition, as this electrode active material (positive electrode active material or negative electrode active material), those mentioned above can be used.

[0092] The surface of the electrode active material refers to the outermost surface of the electrode active material. In addition, the coating process refers to the process of coating at least a portion of the surface. Therefore, the coating glass layer can be configured as the outermost layer in a manner that covers at least a portion of the surface of the electrode active material.

[0093] The coating rate of the coating glass layer formed by coating the lithium ion conductive glass material of the present invention on the surface of the electrode active material can be 18% or more, preferably 20% or more, more preferably 25% or more, and further preferably 30% or more.

[0094] Here, the "coating ratio" refers to the ratio of the area having the coating glass layer on the entire surface of the electrode active material. Specifically, it is the ratio obtained by performing elemental analysis on the outermost layer (the portion with a thickness of several nm to tens of nm from the outermost layer) of the electrode active material having the coating glass layer by X-ray photoelectron spectroscopy (XPS, for example, using VersaProbeII manufactured by ULVAC-PHI), calculating the sum of the quantitative conversion values ​​of the elements in the coating glass layer by calculating the composition of the electrode active material and the composition of the coating glass layer (the lithium ion conductive glass material of the present invention), and then dividing the sum by the sum of the quantitative conversion values ​​of all the elements detected. It should be noted that, for example, when the elements of the coating glass layer such as oxygen overlap with the elements of the electrode active material, the ratio of the other elements (elements that do not overlap with the electrode active material) expected to be the largest in the composition of the coating glass layer except Li is given priority, and the conversion is performed based on the detection value of the other elements and the composition (molar ratio) of the coating glass layer, and the excess amount obtained by the conversion is subtracted from the sum of the elements contained in the composition of the coating glass layer. In addition, in the calculation of the coating rate, gases that can be expected to be adsorbed gases such as carbon dioxide are not excluded.

[0095] Furthermore, the electrode active material of the coated glass layer formed by coating the lithium ion conductive glass material of the present invention on the surface is preferred because it is easy to form a good interface when used in an all-solid-state secondary battery. In addition, if it is used in a liquid lithium ion secondary battery, it is also easy to suppress its cycle degradation, etc., so it is preferred. That is to say, a preferred lithium ion secondary battery (all-solid-state secondary battery or liquid lithium ion secondary battery using a liquid electrolyte) containing the following electrode active material can be obtained: the electrode active material has a coated glass layer formed by coating the lithium ion conductive glass material of the present invention on the surface.

[0096] <Method for producing lithium ion conductive glass material>

[0097] Next, the method for producing the lithium ion conductive glass material of the present invention will be described.

[0098] The lithium ion conductive glass material of the present invention can be manufactured using the usual method for manufacturing amorphous inorganic materials such as firing, melting, and vitrification of inorganic materials. That is, the specified inorganic raw materials are weighed and evenly mixed, and then placed in a crucible made of alumina, quartz, gold or platinum, and the temperature is raised to 750°C to 1450°C, and the temperature is maintained for 30 minutes to 4 hours for melting. The molten glass obtained by melting is poured and then cooled by slow cooling or water cooling. It should be noted that the melting temperature is preferably above 1000°C, and more preferably above 1000°C and below 1300°C, although not limited thereto. The inorganic materials used in the manufacture are not limited, and lithium phosphate (Li3PO4), lithium metaphosphate (LiPO3), orthophosphoric acid (H3PO4), aluminum phosphate (Al(PO3)3), silicon dioxide (SiO2), niobium pentoxide (Nb2O5), germanium dioxide (GeO2), etc. are preferably used.

[0099] The embodiment described above is only an example for easy understanding of the present invention and does not limit the present invention. That is, the components, crystal phases, etc. described above can be changed and improved without departing from the purpose of the present invention, and the present invention also necessarily includes its equivalents.

[0100] Hereinafter, embodiments of the present invention will be described; however, the present invention is not limited to the following embodiments, and various modifications can be made within the technical concept of the present invention.

[0101] Example

[0102] according to Figure 1 In step 1 of the synthesis flow chart shown in the figure, a lithium ion conductive glass material (lithium ion conductive glass sintering aid) is prepared. Figure 1 In step 2 of the synthesis flow chart shown in the figure, a mixed sintering test (production of solid electrolyte) of a lithium ion conductive glass material and a lithium ion conductive material was conducted in real time to simulate the interface formation of an all-solid-state secondary battery. In addition, a coating test of the lithium ion conductive glass material coated on an electrode active material and a charge and discharge test of a half-cell using the electrode active material were also conducted.

[0103] <Manufacturing of lithium-ion conductive glass materials>

[0104] First, lithium phosphate (Li3PO4), lithium metaphosphate (LiPO3) and aluminum phosphate (Al(PO3)3) are prepared in a stoichiometric ratio as shown in Table 1 below, based on mol% of the oxide. The mixture is placed in a platinum crucible, melted and vitrified at a temperature above 1100°C while being fully stirred, and then poured onto a metal casting plate to obtain various lithium ion conductive glass materials of Comparative Examples 1 to 3 and Examples 1 to 5 as amorphous materials. In addition, as glass for evaluating lithium ion conductivity, a glass is prepared in which the melted and vitrified glass is sandwiched between casting plates to be formed into a plate shape. The yield of each lithium ion conductive glass material recovered, including the glass attached to the platinum crucible, is 99% or more by weight. After pouring, each lithium ion conductive glass material is crushed using an impact mill until it passes through a sieve opening of less than 106μm. The relationship between the P2O5 content (mol%) and the Li2O content (mol%) in each lithium ion conductive glass material produced is as follows: Figure 2 As shown in Figure 2, the relationship between Al2O3 content (mol%) and Li2O content (mol%) is Figure 3 In Examples 1 to 5, the Li2O content was adjusted within the range of 47.0% to 55.0 mol%, the P2O5 content was adjusted within the range of 43.5% to 49.0 mol%, and the Al2O3 content was adjusted within the range of 0.5% to 4.0 mol%.

[0105]

Table 1

[0106]

[0107] As basic physical property evaluations of each of the produced lithium ion conductive glass materials, lithium ion conductivity and thermal properties were evaluated.

[0108] The lithium ion conductivity was measured by forming gold electrodes as blocking electrodes on both sides of each plate-shaped lithium ion conductive glass material using a magnetron sputtering device (manufactured by SANYU Electronics, SC-701HMC), and using an electrochemical evaluation device (manufactured by BioLogic, SP300) to perform impedance measurement at 25°C under the conditions of a frequency of 0.1 Hz to 7 MHz, an amplitude voltage of 10 mV, and an open circuit voltage to calculate the lithium ion conductivity.

[0109] The results are shown in Table 2. In addition, the relationship between the Li2O content (mol%) in each lithium ion conductive glass material and its lithium ion conductivity is shown in Figure 4 The lithium ion conductivity of the lithium ion conductive glass materials of Examples 1 to 5 is 8×10 -9 ~3×10 -8 S / cm. On the other hand, among the comparative examples, Comparative Example 2 is higher at 5.8×10 -8S / cm, while Comparative Examples 1 and 3 are lower, less than 5×10 -9 S / cm.

[0110] Thermal properties were measured by differential scanning calorimetry using TG-DTA2000SA manufactured by Bruker Corporation to determine the glass transition point (Tg), crystallization temperature (Tc), and melting onset temperature (mp).

[0111] The results are also shown in Table 2. In addition, the relationship between the crystallization temperature (Tc) and the melting start temperature (mp) of each lithium ion conductive glass material is shown in Figure 5 As shown in Figure 2, the relationship between the crystallization temperature (Tc) and the glass transition point (Tg) is Figure 6 As for Examples 1 to 5, the glass transition point (Tg) is within the range of 330°C to 365°C, the crystallization temperature (Tc) is within the range of 400°C to 460°C, and the melting start temperature (mp) is within the range of 560°C to 590°C.

[0112]

Table 2

[0113]

[0114] <Mixed sintering test of lithium ion conductive glass material and lithium ion conductive material>

[0115] In addition, in order to compare the performance of these lithium-ion conductive glass materials, the interface formation during the sintering of all-solid-state secondary batteries was simulated, such as Figure 1 As shown in step 2, the lithium ion conductive glass material (sintering aid) and the lithium ion conductive material (Li 1.3 Al 0.3 Ti 1.7 P3O 12 : Lithium ion conductive glass ceramics) were mixed and pulverized and sintered at low temperature to prepare solid electrolytes using Comparative Examples 1 to 3 as sintering aids, namely Comparative Examples 4 to 6, and solid electrolytes using Examples 1 to 5 as sintering aids, namely Examples 6 to 10. Specifically, the preparation was carried out according to the following steps.

[0116] The lithium ion conductive glass materials and lithium ion conductive materials (Li 1.3 Al 0.3 Ti 1.7 P3O 12 ) are crushed to less than 106 μm, and then mixed with 12 wt% of lithium ion conductive glass material and 88 wt% of lithium ion conductive material, and 1-propanol is added. Zirconia beads (YTZ beads, manufactured by Nichikatao Co., Ltd.) and a 500cc zirconia crucible were crushed and mixed in a planetary ball mill at 250 rpm for 2 hours (5 minutes of crushing and 1 minute of pause). The crushed slurry was separated from the zirconia beads using a sieve, and the obtained slurry was dried using a ladder-type solvent recovery dryer (manufactured by Sozo Chemical Industry Co., Ltd.).

[0117] The dried mixed powder was crushed using an alumina mortar and an alumina pestle until it passed through a 500 μm sieve, and 1.5 g was taken and used The molding die was molded under a pressure of 20 kN to obtain a plurality of particles for measuring lithium ion conductivity.

[0118] After the particles for measuring lithium ion conductivity were heat treated at 700°C for 1 hour in the atmosphere to obtain sintered particles as solid electrolytes, the lithium ion conductivity was calculated for them using the same method as the lithium ion conductive glass material described above. In addition, the surface of each sintered particle was ground and dried using #800 and #2000 water-resistant sandpaper and 1-propanol, and the diameter, thickness, and weight were measured using a vernier caliper, a micrometer, and an electronic balance to calculate the density. The results are shown in Table 3 below. In addition, the relationship between the lithium ion conductivity and density of each sintered particle is shown in Table 3. Figure 7 Shown in.

[0119]

Table 3

[0120] <![CDATA[Density (g / cm 3 )]]> Lithium ion conductivity (S / cm) Comparative Example 4 2.66 <![CDATA[4.8×10 -5 ]]> Comparative Example 5 2.34 <![CDATA[1.1×10 -4 ]]> Comparative Example 6 2.36 <![CDATA[4.9×10 -5 ]]> Example 6 2.59 <![CDATA[9.4×10 -5 ]]> Example 7 2.70 <![CDATA[1.1×10 -4 ]]> Example 8 2.74 <![CDATA[8.4×10 -5 ]]> Example 9 2.56 <![CDATA[8.3×10 -5 ]]> Example 10 2.69 <![CDATA[1.2×10 -4 ]]>

[0121] In any of the positive electrode layer, negative electrode layer, and electrolyte layer of an all-solid-state secondary battery, it is important to balance the high density required for forming an interface and the high lithium ion conductivity required for conducting lithium ions. Figure 7 As shown, it can be confirmed that compared with Comparative Examples 4 to 6, Examples 6 to 10 are within the range of both high density and high lithium ion conductivity (approximately Figure 7 within the range enclosed by the dotted line).

[0122] In addition, it can be confirmed that the density of the sintered body particles is particularly related to the P2O5 content of the lithium ion conductive glass material used, and is also related to the Li2O content. The relationship between the P2O5 content (mol%) of the lithium ion conductive glass material used in the production of the sintered body particles and the density of the sintered body particles is as follows: Figure 8 The relationship between the Li2O content (mol%) of the lithium ion conductive glass material used in the preparation of the sintered particles and the density of the sintered particles is shown in FIG. Fig. 9 Shown in.

[0123] First, if Figure 8As shown in FIG. 1 , when the P2O5 content of the lithium ion conductive glass material used is between 44 mol% and 45 mol%, the density of the sintered body particles is 2.6 g / cm 3 When the P2O5 content is lower than 43.5 mol%, the density of the sintered particles drops sharply. When the P2O5 content is lower than 43 mol%, the density of the sintered particles drops to 2.34 g / cm 3 , becomes quite low (Comparative Example 5). That is to say, under such conditions, it is difficult to expect bonding (interface formation) with the positive electrode material or conductive additive, etc. On the other hand, as the P2O5 content increases from 44 mol% to 48 mol%, the density further increases. When the P2O5 content is 48.1 mol%, the density of the sintered body particles reaches a maximum of 2.74 g / cm 3 (Example 8) According to the theoretical density of LATP, it is 2.88 g / cm 3 , the density of glass material is 2.43g / cm 3 And weight ratio calculation, the calculated density is 2.88g / cm 3 That is to say, its filling rate reaches 95%, and its density is very high, so it can be expected to be well bonded with the positive electrode material or conductive additive (interface formation). Moreover, it can be confirmed that when the P2O5 content exceeds 50mol%, the density of the sintered particles decreases to 2.36g / cm 3 Sample (Comparative Example 6).

[0124] Based on this, it is considered that the density of the sintered body particles may also be affected by factors other than the P2O5 content of the lithium ion conductive glass material used, and therefore the influence of the Li2O content was also confirmed. Fig. 9 As shown in FIG. 6 , in Comparative Example 6 in which the Li2O content of the lithium ion conductive glass material used was less than 47%, it was confirmed that the density of the sintered particles became very low, namely, 2.36 g / cm 3 On the other hand, when the Li2O content of the lithium ion conductive glass material used is 47% or more, the density of the sintered particles becomes high, and when the Li2O content is greater than 52%, the density of the sintered particles shows a gradually decreasing trend. Although in Example 9 and Comparative Example 5, in which the Li2O content of the lithium ion conductive glass material used is 53.8%, it can be considered that the influence of the P2O5 content is particularly large, since the Li2O content is also beneficial to the lithium ion conductivity, the relationship between the lithium ion conductivity of the lithium ion conductive glass material used and the density of the sintered particles is also confirmed. This result is Fig.10 When the lithium ion conductivity of the lithium ion conductive glass material used is less than 5×10 -9S / cm (Comparative Examples 1 and 3), the density of the sintered particles is unstable (Comparative Examples 4 and 6). -8 S / cm shows that the sintered particles are around 2.7 g / cm 3 If the lithium ion conductivity of the lithium ion conductive glass material used is further increased, the density of the sintered body particles gradually decreases. In Comparative Example 5, which uses Comparative Example 2 with the highest lithium ion conductivity, the density is as low as 2.34 g / cm 3 Although material diffusion is necessary for high density, in NASICON-type crystals, excessive grain growth leads to grain boundary growth and coarsening of the crystals. The same phenomenon was confirmed in this experiment, and it can be inferred that the lithium ion conductivity of the lithium ion conductive glass material used also contributes to this.

[0125] Furthermore, in order to confirm the state of the bonding interface of the sintered particles, secondary electron images were confirmed. The observation was performed using JSM-IT700HR manufactured by JEOL. It should be noted that the cross-section of the sintered body was observed at an incident voltage of 5 kV, a WD of 10 mm, and a magnification of 30,000 times. It should be noted that any sample is a sintered particle at 700°C. Then, the cross-section of the sintered particles was observed and sorted according to the P2O5 content of the lithium ion conductive glass material used. The results are Fig.11 As shown in the figure. In Comparative Example 5 in which the P2O5 content of the lithium ion conductive glass material used is low, it can be confirmed that each grain grows finely and the degree of bonding is low. On the other hand, in Examples 6 to 10, grain growth and interface bonding can be confirmed. Furthermore, in Comparative Example 4 in which the P2O5 content of the lithium ion conductive glass material used is 50.0 mol%, although the interface is relatively good, in Comparative Example 6 in which the lithium ion conductive glass material with the same P2O5 content is used, it can be confirmed that each grain is relatively fine and the interface between the grains is separated at the grain boundary. It can be inferred that since the amount of Li2O in the lithium ion conductive glass material used is low, the interface bonding is insufficient.

[0126] The lithium ion conductivity of the sintered particles was confirmed to be well correlated with the Al2O3 content of the lithium ion conductive glass material used and its lithium ion conductivity. Fig.12 The relationship between the lithium ion conductivity of the lithium ion conductive glass material used (the ion conductivity of the glass) and the lithium ion conductivity of the sintered body particles is shown in FIG. Fig.13As shown in FIG. 1 . Regarding the Al2O3 content of the lithium ion conductive glass material used, the lithium ion conductivity of the obtained sintered body particles increases even if a small amount is contained, and although it becomes better at 0.5 mol% or more, the conductivity decreases at a position where the Al2O3 content exceeds 4.0 mol%. The lithium ion conductivity of the lithium ion conductive glass material used is highly correlated with the lithium ion conductivity of the sintered body particles. Based on the above, it can be inferred that the lithium ion conductive glass material melts during sintering and becomes present at the interface between LATPs, but when its lithium ion conductivity becomes less than 5×10 -9 S / cm, it can be confirmed that the lithium ion conductivity of the sintered particles tends to decrease.

[0127] It should be noted that, since the physical properties of the lithium ion conductive glass material used showed that when the lithium ion conductivity was too low, the lithium ion conductivity of the sintered particles decreased, and when the lithium ion conductivity was too high, the density of the sintered particles decreased, the thermal properties of the lithium ion conductive glass material used and the trends of the lithium ion conductivity and density of the sintered particles were further confirmed. Fig.14 , Fig.15 as well as Fig.16 As shown in. Examples 6 to 10 made using a lithium ion conductive glass material that satisfies any one of the ranges of glass transition point (Tg) of 330°C to 365°C, crystallization temperature (Tc) of 400°C to 460°C, and melting start temperature (mp) of 560°C to 590°C can confirm that both density and lithium ion conductivity have high values. On the other hand, in the comparative examples, Comparative Example 4 made using a lithium ion conductive glass material having a Tg of 325.0°C, a Tc of 387.2°C, and an mp of 637.0°C has a relatively high density of 2.66 g / cm 3 , but its lithium ion conductivity is low at 4.8×10 -5 S / cm. The Tc is 463.9℃ and the lithium ion conductivity is 5.8×10 -8 S / cm lithium ion conductive glass material, although its lithium ion conductivity is relatively high at 1.1×10 -4 S / cm, but its density is lower at 2.34g / cm 3 Comparative Example 6, which was made of a lithium ion conductive glass material with a Tg of 367.4°C, a Tc of 470.9°C, and an mp of 640.8°C, had a lower density of 2.36 g / cm 3 , its lithium ion conductivity is also low at 4.9×10 -5 S / cm.

[0128] Based on the above, it can be confirmed that by using a lithium ion conductive glass material having a specified composition and having specified thermophysical properties (Tg, Tc, mp) and lithium ion conductivity as a sintering aid, sintered particles with high density and high lithium ion conductivity, which are necessary for interface formation in all-solid-state secondary batteries, can be obtained.

[0129] <Coating test of lithium ion conductive glass material on electrode active material>

[0130] The above-prepared lithium ion conductive glass material was dispersed in water and then diluted with 1-propanol to prepare a glass material dispersion, which was then coated on the electrode active material, and the hydration water during the preparation of the dispersion was removed by subsequent drying and heat treatment, and a coating test was carried out in this manner. Specifically, the following steps were performed.

[0131] (1) Preparation of glass material dispersion

[0132] 5 g of the lithium ion conductive glass material of Comparative Example 1, Comparative Example 2 and Example 5 were placed in a 100 ml beaker, 95 g of water and a stirrer were added and stirred for more than 48 hours to disperse the lithium ion conductive glass material in water. 30 g of 1-propanol was added to 10 g of the stirred solution and stirred to prepare a glass material dispersion.

[0133] (2) Coating treatment

[0134] Put 5g of graphite (SGP25, manufactured by SEC Carbon: Comparative Example 7, Comparative Example 8, Example 11) or 45g of LiMn2O (spinel lithium manganese oxide, manufactured by Honjo Chemical Co., Ltd.: Example 12) and 20g of the above-mentioned glass material dispersion in a container, and add 250g of 5mm beads, and use a mixer (ADM-50, manufactured by THINKY) to grind for 5 minutes × 3 groups at 1000rpm. The pause time between 1 group is more than 5 minutes. After grinding, use a SUS sieve with a pore size of 1.7mm to separate the beads, and transfer the slurry to a SUS tray and dry it in a nitrogen atmosphere for 90 minutes.

[0135] (3) Preparation of Comparative Products without Coating

[0136] For comparison, a glass particle mixed sample with the same weight ratio without coating treatment was also prepared (Comparative Example 9). A planetary ball mill (P-5, manufactured by Fritsch) was used to micronize the lithium ion conductive glass material. 30 g of 1-propanol was added to 10 g of the lithium ion conductive glass material in Example 5, and the mixture was crushed at 250 rpm using a φ2 mm YTZ ball in a zirconia container. Then, 1 g of the crushed solution and 19 g of 1-propanol were added to the above 5 g of graphite, and then 250 g of 5 mm beads were added, and the mixture was crushed at 1000 rpm for 5 minutes × 3 groups using a mixer (ADM-50, manufactured by THINKY). The pause time between groups was 5 minutes or more. After the crushing, the beads were separated using a sieve made of SUS with an aperture of 1.7 mm, and the slurry was transferred to a tray made of SUS and dried in a nitrogen atmosphere for 90 minutes.

[0137] (4) Heat treatment

[0138] All samples were dried and placed in an alumina mortar, and heat-treated at 400° C. for 10 minutes in a nitrogen atmosphere. For the samples subjected to the coating treatment, water bound to the glass was removed during the heat treatment.

[0139] The coating rate of each sample was analyzed by X-ray photoelectron spectroscopy (XPS, VersaProbeII manufactured by ULVAC-PHI). The X-ray source was Al-Kα (1486.6 eV), the X-ray diameter was 100 μm (25 W 15 kV), and the analysis area was a point of φ100 μm.

[0140] The results (detected elements and their quantitative conversion values, coating rates) and the calculation formula for the coating rate based on the quantitative conversion values ​​of the detected elements are shown in Table 4 below. It should be noted that no correction for the adsorption of CO2 was performed. Regarding Example 11, in which the negative electrode active material (graphite) was coated with a lithium ion conductive glass material, the coating rate was significantly increased and exceeded 20% compared with the mixed sample of Comparative Example 9 (a small amount of lithium ion conductive glass material was physically set on the surface of the graphite). In addition, regarding Example 12, in which the positive electrode active material (spinel-type lithium manganese oxide) was coated with a lithium ion conductive glass material, there was a coating rate of 58.9%. On the other hand, regarding Comparative Examples 7 and 8, due to the influence of the composition of the lithium ion conductive glass material, etc., the coating rate was low, less than 18%.

[0141]

Table 4

[0142]

[0143] <Charge and discharge test>

[0144] In order to confirm the effect of coating the negative electrode active material with the lithium ion conductive glass material, half cells were prepared using Comparative Example 9 and Example 11, and charge and discharge tests were performed. Specifically, the following test was performed.

[0145] A mixture (binder) of 10% polyvinylidene fluoride (PVdF) mixed with Comparative Example 9, Example 11 or untreated graphite (SGP25) was coated, dried and compacted to prepare a composite electrode. The electrolyte used was 1 mol·dm -3 -LiPF6 / ethylene carbonate+dimethyl carbonate (volume ratio 1:1), a polyolefin separator was used as the separator, and the half-cells of Comparative Examples 10 to 11 and Example 13 shown in Table 5 below were prepared. Then, they were subjected to charge and discharge tests to confirm the change in charge and discharge capacity, and the reversible capacity rate of the first cycle ((discharge capacity / charge capacity)×100%) was calculated.

[0146] The results are shown in Table 5 below. The reversible capacity rate of the first cycle of the half-cell of Comparative Example 10 using graphite without adding the lithium ion conductive glass material was 90%. In addition, the reversible capacity rate of the first cycle of the half-cell of Comparative Example 11 using Comparative Example 9 in which only the lithium ion conductive glass material and the negative electrode active material were dispersed and mixed was not improved. On the other hand, the reversible capacity rate of the first cycle of the half-cell of Example 13 using graphite coated with the lithium ion conductive glass material was significantly improved to 97%, which confirmed the usefulness of the coating treatment.

[0147]

Table 5

[0148] Negative active material Reversible capacity rate of the first cycle (%) Comparative Example 10 SGP25 90 Comparative Example 11 Comparative Example 9 90 Embodiment 13 Embodiment 11 97

[0149] The present invention claims the benefit of priority based on Japanese patent application No. 2022-099569, filed on Jun. 21, 2022, the disclosure of which is incorporated herein in its entirety.

Claims

1. A lithium ion conductive glass material, comprising, in terms of mol% based on oxide: 43.5~49.0% P2O5 component, 0.5~4.0% Al2O3 content, 47.0~55.0% Li2O composition.

2. The lithium ion conductive glass material according to claim 1, wherein: Satisfies at least two or more selected from the group consisting of (1), (2) and (3) below, and has a lithium ion conductivity of 5.0×10 -9 S / cm or more 5.0×10 -8 S / cm or less, (1) The crystallization temperature (Tc) is 400°C to 460°C; (2) Glass transition point (Tg) is above 330°C and below 365°C; (3) The melting start temperature (mp) is 560°C or higher and 590°C or lower.

3. The lithium ion conductive glass material according to claim 1 or 2, wherein: The lithium ion conductive glass material is a crystalline phase of a NASICON structure including a rhombohedral crystal system, Li 1+x Al x Ti 2-x P3O 12 (0.7>x≥0.05) crystalline phase, or Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 The sintering aid used in the mixed sintering of the lithium ion conductive material having a crystalline phase (0.7>x≥0.05, 0.5>y≥0) is a powder having a maximum particle diameter of 200 μm or less and an average particle diameter (D50) of 100 μm or less.

4. A solid electrolyte material obtained by mixing the lithium ion conductive glass material according to claim 1 or 2 with a lithium ion conductive material, wherein the lithium ion conductive material comprises: a crystal phase of a rhombohedral NASICON structure, a Li 1+x Al x Ti 2-x P3O 12 A crystalline phase of (0.7>x≥0.05), or a crystalline phase of Li1+x+yAlxTi2-xSiyP3-yO12 (0.7>x≥0.05, 0.5>y≥0).

5. An all-solid-state secondary battery comprising a component integrally formed by sintering a material comprising the solid electrolyte material according to claim 4 and a positive electrode material or a negative electrode material.

6. An electrode active material comprising a coating glass layer formed by coating the lithium ion conductive glass material according to claim 1 or 2 on a surface, wherein a coating rate of the coating glass layer on the surface is 18% or more. 7 . A lithium ion secondary battery comprising the electrode active material according to claim 6 .

Citation Information

Patent Citations

  • All-solid secondary battery

    JP2012209256A

  • Glass electrolyte and all-solid lithium ion secondary battery

    JP2015153588A

  • Outer wall panel fixture and outer wall panel fixing method

    JP2022099569A